Pengetahuan Matematika Dalam Al-Qur’an - Wandini, Rora Rizki; Rahayu, Rahayu; Fitriani, Fitriani (Peneliti.net, 2024)
The Qur'an contains scientific passages that offer mathematical instructions, serving as a source of scientific knowledge. The objective of this book is to attain a more profound comprehension of the mathematical data contained within the Qur'an. The literature review is the main research technique adopted in this study, focusing on scientific works that analyze mathematical information in the Qur'an. These works are supported by additional relevant material from other books or sources written by other writers. As per this study, the Qur'an encompasses several mathematical concepts, such as arithmetic procedures. The user's text is incomplete.Surah Al-A'raf (7): 142, Surah Al-Baqarah (2): 196, Surah Al-Kahf (18): 25, Surah Al-Muzammil (Chapter 73), verses 3-4, Surah Al-Ankabut (29): 14, Surah Al-Baqarah (2): 261, Surah Al-An'am (6): 160, Surah Al-Muzammil (73): 20, Surah An-Nisa' (4): 12), and Surah Al-Fathir (35): 1 and Surah An-Nur (24): 45, Surah Al-An'am (6): 128, Surah Al-Baqarah (2): 97. Verse references for the following chapters: Al-Waqiah (56): 7-10, Taha (20): 6, Az-Zumar (38): 9, Lukman (31): 20. Estimation mentioned in Ash-Shaffat (37): 174. Row count mentioned in Ash-Shaff (61): 4, An-Naml (27): 17. Cartesian multiplication mentioned in Al-Baqarah (2): 261. Enumeration and integers mentioned in Al-Fajr (89): 2-3, Al-Isra' (17): 12. This branch of mathematics is considered a means to demonstrate the magnificence of Allah Swt via His many creations.